High flow nasal oxygen in resource constrained, non-intensive care high care wards for COVID-19 acute hypoxaemic respiratory failure: comparing outcomes of first versus third waves - Audley, Gordon George (Department of Medicine, 2024)
Background: High flow nasal oxygen (HFNO) is an accepted treatment for severe COVID-19 related acute hypoxaemic respiratory failure (AHRF) especially where limited access to intensive care unit (ICU) resources exists, and approximately halves the need for invasive mechanical ventilation. Objectives: To determine if treatment outcomes would be better in the third COVID wave (irrespective of differences in variant virulence; ancestral vs delta) due to increased institutional experience and capacity for HNFO and more restrictive admission criteria for respiratory high care wards and ICU dictated by the higher case load in the third wave. Methods: We included consecutive patients with COVID-19-related AHRF treated with HFNO during the first (7 May to 25 August 2020) and third COVID waves (4 July to 4 September 2021) at Groote Schuur Hospital. The primary endpoint was comparison of HFNO failure between the first and third waves of the COVID-19 pandemic. Findings: A total of 744 patients were included: 343 in the first, and 401 in the third COVIDwave. Patients treated with HFNO in the first wave had an older median (IQR) age (53 (46-61) vs 47 (40-56) years, p<0.001), and a higher prevalence of diabetes (46.9 vs. 36.9%, p=0.006), hypertension (51.0% vs 35.2%, p<0.001), obesity (33.5% vs 26.2%, p=0.029) and HIV infection (12.5% vs 5.5%, p<0.001). Median (IQR) arterial oxygen partial pressure to fraction inspired oxygen ratio (PaO2/FiO2) at HFNO initiation and the ratio of oxygen saturation/FiO2 to respiratory rate within 6 hours (ROX-6 score) after HFNO commencement were lower in the first wave compared with the third: 57.9 (47.3-74.3) vs 64.3 (51.2-79.0), p=0.005 and 3.19 (2.37-3.77) vs 3.43 (2.93-4.00), p<0.001, respectively. Despite these differences in comorbidities and baseline measures of oxygenation, the likelihood of HFNO failure (57.1% versus 59.6.1%, p=0.498) and mortality (52.1% vs 46.9%, p=0.159) did not differ between first and third waves the first and third COVID waves. Conclusion: Despite differences in overall case load, baseline patient characteristics, virulence of the circulating wave variant and institutional experience with HFNO, treatment outcomes were very similar in the first and third COVID waves. We conclude that once severe respiratory failure is established in COVID pneumonia, comorbidities and HFNO provider experience make little difference to outcome.